2015
DOI: 10.4038/jula.v18i2.7864
|View full text |Cite
|
Sign up to set email alerts
|

Use of Information and Communication Technologies (ICTs) by University Freshmen: With Special Reference to the University of Moratuwa

Abstract: New coming students for universities are fundamentally different than in the past, because they have been spending their entire lives surrounded by and using ICTs. These students belong to the net generation and always looking for ICTs in each and every activity of their life. However, it is questioned whether all students are in the same level since they should be very fluent with ICTs to move in this 21 st century confidently. This study is an attempt made to investigate the level of using ICTs by new coming… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…Data collection was done via a questionnaire distributed among 338 freshmen. Findings demonstrated that the first year students as digital natives were rapidly inclined towards high ICT usage (Kumara, 2014). It was revealed that majority of respondents perceived themselves as highly skilled in using computer applications.…”
Section: Literature Reviewmentioning
confidence: 93%
See 1 more Smart Citation
“…Data collection was done via a questionnaire distributed among 338 freshmen. Findings demonstrated that the first year students as digital natives were rapidly inclined towards high ICT usage (Kumara, 2014). It was revealed that majority of respondents perceived themselves as highly skilled in using computer applications.…”
Section: Literature Reviewmentioning
confidence: 93%
“…Regarding ICT usage and computer literacy skills male students surpassed female students. In addition, most of the new students believed that ICTs were helpful to enhance their learning.The results of the study would aid in developing existing programs and implementing new programs effectively for new students (Kumara, 2014).In an attempt to explore characteristics and information seeking behavior of students, Mashroofa (2012) also used new comers from three Sri Lankan universities as research subjects. Data were collected via a survey and analyzed using qualitative as well as quantitative methods.…”
Section: Literature Reviewmentioning
confidence: 99%